General high-order rogue waves in the Hirota equation. (June 2023) - Wang, Tingyou; Qin, Zhenyun; Mu, Gui; Zheng, Fuzhuang
Abstract: In this work, we focus on the construction of N th-order rogue waves for the Hirota equation by utilizing the bilinear method and Kadomtsev–Petviashvili (KP) hierarchy reduction technique. The formula can be represented in terms of determinants whose matrix elements are related to Schur polynomials. In addition, some interesting dynamic patterns of rogue waves are exhibited analytically and graphically. Highlights: Rogue waves of Hirota equation are reduced to results by bilinear method and KP reduction technique. A new method of concluding bilinear equation is shown. Some interesting dynamic patterns of rogue wave are exhibited analytically and graphically.